THE USE OF MODERN TEACHING TECHNOLOGIES IN THE EDUCATIONAL PROCESS (Web of Technology: Multidimensional Research Journal, 2024)
This article discusses the use of modern information technology and didactic tools in the educational process. The advantages of the use of didactic game technologies in the development of independent and creative abilities of students, increasing their interest in the lesson are emphasized.